Public opinion feedback between elections, and stability of single-party majority governments. (December 2015) - Matsumoto, Tomoko; Laver, Michael
Abstract: Why would a mid-term slump in public support destabilize a single-party government with a secure majority in parliament? We argue here that the answer can be found in the internal politics of the government party. Faced with declining government popularity, ordinary legislators in the government party, who above all fear loss of their seats, may withdraw support from the party leadership and thereby destabilize the government. We set out an informal model that suggests how, if public opinion shocks have different implications for different classes of politician in the government there may be well-specified circumstances in which these can destabilize a single party majority cabinet. We assess these theoretical conclusions using public opinion data from Japan. Highlights: An informal model implying that public opinion feedback between elections can destabilize single-party majority cabinets. Replacements of LDP governments in Japan are more likely when the popularity of party leaders lags behind that of the party. Early dissolutions are more likely when support for the main opposition party is rising.